2023
DOI: 10.1002/cb.2263
|View full text |Cite
|
Sign up to set email alerts
|

Have I purchased the right product? Consumer behavior under corporate greenwash behavior

Cheng‐Ze Hung,
Tai‐Wei Chang

Abstract: Extensive research on corporate greenwash behavior has been conducted within sustainable consumption, yet aware of green product information asymmetry remains largely unexplored. Drawn upon value‐attitude‐behavior hierarchy, this study investigates the impact of corporate greenwash behavior on green purchase behavior among customers in Taiwan, with a particular focus on the mediating role of green trust and environmental attitudes and on the moderating role of green product information asymmetry. Customers pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…Accordingly, our results refine those of Chang et al (2021), who stated that information asymmetry does not directly influence green product purchasing behavior but must go through product packaging and consumer psychology. In addition, this study supports the findings of Hung and Chang (2023), who explained that information asymmetry positively moderates the relationship between environmental attitudes and green purchasing behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, our results refine those of Chang et al (2021), who stated that information asymmetry does not directly influence green product purchasing behavior but must go through product packaging and consumer psychology. In addition, this study supports the findings of Hung and Chang (2023), who explained that information asymmetry positively moderates the relationship between environmental attitudes and green purchasing behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Chang et al (2021) found that green product information asymmetry does not affect green product purchasing behavior. In addition, Hung and Chang (2023) found that green product information asymmetry strengthens the positive relationship between environmental attitudes and green purchasing behaviors. Therefore, we propose the following hypothesis:Hypothesis Green product information asymmetry positively affects green product purchase behavior.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Have I purchased the right product? This is the inquiry of Hung and Chang (2024), who delve into the impact of corporate greenwash behaviour on green purchase behaviour in Taiwan. They explore the mediating role of green trust and environmental attitudes and the moderating role of green product information asymmetry.…”
Section: Consumer Behaviour‐based and Marketing Strategic Perspectivesmentioning
confidence: 99%
“…Studies in the special issue suggest exploring how digital platforms facilitate new consumption models and the role of technology in sustainable practices (Thaichon et al, 2024). Future research focusing on effective educational interventions and the impact of marketing and informational campaigns on behaviour change is crucial (Hung & Chang, 2024; Thaichon et al, 2024).…”
Section: Consumer Behaviour‐based and Marketing Strategic Perspectivesmentioning
confidence: 99%
“…Environmental policy requirements [13] and consumer demand [3] have become important greenwashing drivers. From an information economics view, consumers have limited green market cognition, causing information asymmetry [14]. Imperfect regulations enable greenwashing through certification loopholes [15].…”
mentioning
confidence: 99%